Manajemen Laba dan Penghindaran Pajak Perusahaan Sektor Pertambangan - Arizah, Ainun; Ayudina, Rika; Muchran, Muchriana; Arsal, Muryani (Owner : Riset dan Jurnal Akuntansi, 2024)
This study aims to determine the effect of earnings management on tax avoidance and to see differences in earnings management practices and tax avoidance before and during the COVID-19 pandemic. The population in this study are mining sector companies listed on the Indonesia Stock Exchange (IDX) for the 2018-2021 period. The selected sample consists of 14 mining companies obtained from purposive sampling technique. This type of research is quantitative, secondary data comes from annual financial reports. Based on the results of data research using STATA 16 Software, the results show that (1) there is no effect between earnings management on tax avoidance (2) there are differences in earnings management practices before and during the pandemic, with the results before the pandemic earning management practices of -0.116, while during the pandemic by -0.030. these results show that earnings management practices were much higher before the pandemic (3) there was no difference in the level of tax avoidance practices before and during the Covid-19 pandemic.